2016
DOI: 10.1016/j.scijus.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mark enhancement techniques on the subsequent detection of saliva

Abstract: 1 AbstractPurpose. There appears to be a limited but growing body of research on the sequential analysis/treatment of multiple types of evidence. The development of an integrated forensic approach is necessary to maximise evidence recovery and to ensure that a particular treatment is not detrimental to other types of evidence. This study aims to assess the effect of latent and blood mark enhancement techniques (e.g. fluorescence, ninhydrin, acid violet 17, black ironoxide powder suspension) on the subsequent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…Many studies reported the RSID™-Saliva kit is more sensitive when compared to previously used immunochromatographic identification methods; SALIgAE® and Phadebas® tests (Pang and Cheung, 2008;Casey and Price, 2010). McAllister et al, (2016) recorded better extraction and improvement of the visualisation of saliva deposited on non-porous substrates after usage of enhancement techniques (Cyanoacrylate/BY40, Ironoxide PS and Ninhydrin) prior to extraction by RSID kit. These techniques provide a target area for swabbing for subsequent confirmation and DNA tests.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Many studies reported the RSID™-Saliva kit is more sensitive when compared to previously used immunochromatographic identification methods; SALIgAE® and Phadebas® tests (Pang and Cheung, 2008;Casey and Price, 2010). McAllister et al, (2016) recorded better extraction and improvement of the visualisation of saliva deposited on non-porous substrates after usage of enhancement techniques (Cyanoacrylate/BY40, Ironoxide PS and Ninhydrin) prior to extraction by RSID kit. These techniques provide a target area for swabbing for subsequent confirmation and DNA tests.…”
Section: Discussionmentioning
confidence: 92%
“…The saliva samples were obtained after at least an hour of brushing teeth and eating or drinking anything. This was to ensure that the samples were collected under near constant conditions, to minimise the variation in amylase concentrations and to remove food residue (McAllister et al, 2016).…”
Section:  Inclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Saliva spots are usually not clear from visual assessment (McAllister, 2016). However, some types of evidence often include saliva marks such as drinking containers, cigarette butts, chewing gum, and adhesive surfaces of envelopes, bite marks, and nylon masks.…”
Section: Sputum Testmentioning
confidence: 99%
“…There is a growing body of literature assessing the impact of multiple types of analysis [1][2][3][4] A sequential order for treating multiple types of evidence should be established to maximise the evidence recovery. If a biological stain is not visible, speculative swabbing may be detrimental to any latent marks present.…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%